Are Quine’s criteria of adequacy for individuations unduly restrictive? - Greimann, Dirk (Universidad de Costa Rica, 2018)
An important principle guiding Quine’s ontology consists in the rejection of ‘entities without identity’. It is used by him to reject intensional and merely possible entities. But Quine has never made explicit what the criteria are that a given sort of entities must meet in order to count as ‘well-individated’ in his sense. In section 1 of this paper, these criteria are reconstructed. Section 2 aims to show that these criteria are unduly restrictive: they imply that even the entities of Quine’s own ontological system lack identity. In section 3, it is argued that the prospects of constructing a less restrictive standard are dim. From this the conclusion is drawn that Quine’s distinction between entities with and without identity is idle. It is a distinction without a difference and must hence be rejected.